Minimum wage and firm employment: Evidence from China - Yi Huang; Prakash Loungani; Gewei Wang (Graduate Institute of International and Development Studies, 2014)
This paper studies how minimum wage policies affect firm employment in China using a unique county level minimum wage data set matched to disaggregated firm survey data. We investigate both the effect of imposing a minimum wage, and the effect of the policies that tightened enforcement in 2004. We find that the average effect of minimum wage changes is modest and positive, and that there is a detectable effect after enforcement reform. Firms have heterogeneous responses to minimum wage changes which can be accounted for by differences in their wage levels and profit margins: firms with high wages or large profit margin increase employment, while those with low wages or small profit margin downsize. The increase in enforcement of Chinas minimum wage in 2004 has since amplified this heterogeneity, which implies that labor regulation may reduce the monopsony rent of firms.Our results provide evidence for the theoretical predictions of the positive minimum wage-employment relationship in a monopolistic labor market.
Keywords: J24; J31; O14; F10; F14; 330; China; employment; minimum wages; heterogeneous effect